LIBRARY AUTOMATION IN UNIVERSITIES AND COLLEGES LIBRARIES IN INDIA AND ABROAD - Nimbhorkar, Sarala P. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Library automation has become integral to managing and enhancing library services in universities and colleges worldwide. This study examines the application and impact of library automation in higher education libraries in India and abroad, focusing on technological advancements, implementation challenges, and the comparative benefits of automation across different institutional contexts. Library automation aids in streamlining processes, reducing human error, and improving user access to vast information resources. This case study analyzes various library automation systems, evaluates their effectiveness, and assesses how these technologies impact library users and staff in academic settings.